The Impact of Emotional Maturity and Social Problem-Solving Abilities on Neurobehavioral Outcomes in Autistic Adolescents - Parsakia, Kamdin (Psychological Research in Individuals with Exceptional Needs, 2023)
This study aims to investigate the predictive value of emotional maturity and problem-solving skills on neurobehavioral functioning in adolescents with autism. A cross-sectional design was employed, involving 282 adolescents aged 12-18 diagnosed with autism spectrum disorder (ASD). Participants were assessed using the Behavior Assessment System for Children, Second Edition (BASC-2) for neurobehavioral functioning, the Emotional Maturity Scale (EMS), and the Social Problem-Solving Inventory-Revised (SPSI-R). Pearson correlation analysis and linear regression were conducted using SPSS version 27 to examine the relationships and predictive power of emotional maturity and problem-solving skills on neurobehavioral functioning. Descriptive statistics revealed mean scores of 78.54 (SD = 10.37) for neurobehavioral functioning, 84.29 (SD = 12.51) for emotional maturity, and 81.75 (SD = 11.68) for problem-solving skills. Pearson correlation showed significant positive correlations between neurobehavioral functioning and emotional maturity (r = 0.45, p = 0.001), and problem-solving skills (r = 0.38, p = 0.005). Regression analysis indicated that emotional maturity (B = 0.32, p = 0.001) and problem-solving skills (B = 0.29, p = 0.005) significantly predicted neurobehavioral functioning, explaining 27% of the variance (R² = 0.27). The study demonstrates that higher levels of emotional maturity and problem-solving skills are associated with better neurobehavioral functioning in adolescents with autism. These findings underscore the importance of incorporating emotional and cognitive skill development in interventions to enhance neurobehavioral outcomes for this population. Future research should adopt longitudinal designs to explore these relationships over time and include diverse populations for broader applicability.